2008
DOI: 10.1002/gps.2175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a home‐based exercise program in the treatment of Alzheimer's disease: The Maximizing Independence in Dementia (MIND) study

Abstract: SUMMARY Objective To determine the feasibility and efficacy of a home-based exercise intervention program to improve the functional performance of patients with Alzheimer’s Disease (AD). Methods Twenty-seven home-dwelling patients with AD were randomized to either an exercise intervention program delivered by their caregivers or a home safety assessment control. Measures of functional performance (primary), cognition, neuropsychiatric symptoms, quality of life and caregiver burden (secondary) were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
255
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(270 citation statements)
references
References 22 publications
5
255
1
9
Order By: Relevance
“…Steinberg et al 25 found a non-significant improvement of QoL measured using the Alzheimer's Disease-Related…”
Section: Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Steinberg et al 25 found a non-significant improvement of QoL measured using the Alzheimer's Disease-Related…”
Section: Searchmentioning
confidence: 99%
“…The control group in one study was a home-safety assessment group 25 and in the other, a group of patients that received routine medical care and no intervention. 26 The evaluation of depression, also using the SF-36 ® , revealed that all studies had significant results.…”
Section: Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1. A list of excluded studies [32,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] can be also found in Suppl. Table 2.…”
Section: Resultsmentioning
confidence: 99%